Analysis of Functional Linkages between Research and Extension in Dairying under Different Linkage Systems in Haryana - Dr. Shantanu Kumar; Dr. Uma Sah; Dr. Ram Kumarr (Journal of Agricultural Extension Management, 2025)
The need of functional interaction between knowledge production system and knowledge dissemination system has been identified globally as well as nationally (Anonymous, 1992; Cernea et al. 1985; Prasad, 1988; Venkatesan, 1985). In the similar vein, Lionberger and Chang (1970) also pointed out that more is the meaningful interaction within and between the above systems, faster will be the process of modernization of agriculture. In the field of dairying research and extension(R&E), meaningful interaction between these two is further magnified looking into the cost of research and development facilities for producing superior germplasm and evolving better health services especially disease diagnostic facilities (Acharya, 1994; Singh, 1994). With respect to the effective functional linkage between research and extension, several researchers have argued about effectiveness of functional linkage vis.-a. -vis., their organizational arrangements. There had been debate and deliberation on putting R&E in the same organization or keeping them separately. Bourgeosis (1989), Kessaba (1989), Pineiro (1989) and Antholt ( 1990) have argued for merging R&E in one institution for better linkage. Contrary to them, Trent ( 1989) and Eponou ( 1993) found that R&E integration does not give guarantee of effective link between them. Such international experiences offer ample stimulus to make an empirical probe on differential status of functional linkage. Between research and extension in dairying where both are working in different organizational settings. An investigation was, therefore, carried out with the specific objective to analyze the functional interaction between research and extension in dairying, operating under two organizational systems in the state of Haryana.